-x + y = -13 --------------------(1)
-8x - 4y = -8 -------------------(2)
First, we will eliminate x and then solve for y
Mulltiply through equation (1) by 8
-8x + 8y = -104 --------------------(3)
Subtract equation (3) from equation (2)
-12y = 96
divide both-side of the equation by -12
y = 8
Then, we will go ahead and eliminate y then solve for x
Multiply equation (1) through by 4
-4x + 4y = -52 -------------------(4)
add equation (4) and equation (2)
-12x = -60
Divide both-side of the equation by -12
x = 5